2021
DOI: 10.1186/s12906-021-03322-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of long non-coding RNA CYTOR induced by icariin promotes the viability and inhibits the apoptosis of chondrocytes

Abstract: Background Icariin (ICAR) is the main effective component extracted from epimedium, and is reported to have the potential to treat osteoarthritis (OA). However, its pharmacological function on chondrocytes has not been fully clarified. Methods Different doses of ICAR were used to treat chondrocyte cell lines, including CHON-001 and ATDC5. Then the expressions of different lncRNAs were measured by qRT-PCR. Interleukin-1β (IL-1β) was used to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Flavonols are interesting for their biological activity, such as being antioxidant, antimicrobial, hepatoprotective, and anti-inflammatory, and, more recently, they have also been studied as potential anticancer agents. In our research, we found twelve manuscripts on six molecules: astilbin, galangin (3,5,7-trihydroxyflavone, Gal), hyperoside, icariin, quercetin (Que), and rutin [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Astilbin is a flavonol identified in Dimorphandra mollis , Hypericum perforatum, and other natural plants, and it is also extracted from grapes.…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonols are interesting for their biological activity, such as being antioxidant, antimicrobial, hepatoprotective, and anti-inflammatory, and, more recently, they have also been studied as potential anticancer agents. In our research, we found twelve manuscripts on six molecules: astilbin, galangin (3,5,7-trihydroxyflavone, Gal), hyperoside, icariin, quercetin (Que), and rutin [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Astilbin is a flavonol identified in Dimorphandra mollis , Hypericum perforatum, and other natural plants, and it is also extracted from grapes.…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
“…ICA inhibits IL-1β-induced phosphorylation of PI3K, AKT, and mTOR, and attenuates the excessive production of MMP-3 and promotes the production of Col-II. Silencing ULK1 reverses the protective effect of ICA in OA chondrocytes, demonstrating that ULK1 and the autophagy process are essential for ICA’s mechanism of action [ 70 ]. In Wang et al (2021), ICA induced the expression of an lncRNA, Cytoskeleton Regulator RNA (CYTOR), implicated in age-related articular cartilage degradation.…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
“…Curiously, the upregulated expression of CYTOR has been reported not only in vitro models but also in patients with several breast cancer classes such as HER2 or triple negative carcinomas subtypes [64]. Moreover, emerging evidence has pointed out that CYTOR is not a breast cancer specific lncRNA, showing upregulated expression in several other types of cancer such as nasopharyngeal, gastric, colon, or hepatocellular carcinoma and also correlating with poor prognoses and increased aggressiveness [30,31,[65][66][67][68]. Cytoskeletal dynamics require the participation of several modulating factors which regulate G-actin assembly and de-assembly to form filaments.…”
Section: Lncrnas Modulators Of Actin Filaments and Accessory Proteins...mentioning
confidence: 99%
“…Long non-coding RNA (lncRNA) induced by icariin is also confirmed to promote proliferation and repress the loss of chondrocytes in an inflammatory microenvironment. Cytoskeleton regulator RNA (CYTOR) is a kind of lncRNA, Wang, G. et al ( Wang et al, 2021 ) demonstrated that the CYTOR knockdown could reverse the anti-OA drug’s protective effect in chondrocytes, indicating CYTOR to be a promising chondrocyte-targeted nanodrug for OA.…”
Section: Cartilage Targeted Nanodrugsmentioning
confidence: 99%